Πολέμου καὶ μάχης... (Gorg. 447a1 ss.): Guerra y virilidad en la caracterización de Calicles en el Gorgias de Platón - Moreno González, Rafael (Pontificia Universidad Católica del Perú, 2024)
The initial words of Plato’s Gorgias constitute an important clue to understanding the literary and philosophical characterizations of the figure of Callices inside the Platonic dialogue. The fact that Plato begins with a greeting from Callicles in which war and confrontation are explicitly mentioned shows how important these activities are for this figure. The rest of the dialogue has the function of developing this aspect of Callicles’ soul. Calicles makes clear—both through his words and actions in the ensuing conversation—that he defends a way of life defined by honor and public recognition in the political realm, by the subjugation of others, and by the satisfaction of all kinds of appetites and desires—all considered constitutive elements of a happy life. In this sense, the first words of the dialogue offer us a first glimpse of the figure of Calicles which coheres with his characterization throughout the whole dialogue.

Las palabras iniciales del Gorgias son una pista importante para comprender la caracterización literaria y filosófica del personaje Calicles dentro del diálogo platónico. Así, que Platón colocara en boca de Calicles un saludo donde se mencionan explícitamente la guerra y el enfrentamiento muestra lo importante que estas actividades son para este personaje. El resto del diálogo sirve para desarrollar este aspecto del alma de Calicles, quien, tanto en sus intervenciones como en su accionar en la conversación, deja clara su defensa de un modo de vida definido por el honor y el reconocimiento público en el ámbito político, el sometimiento de otros, así como la satisfacción de toda clase de apetitos y deseos como elementos constitutivos de una vida feliz. En tal sentido, las primeras palabras del diálogo nos ofrecen un primer vistazo del personaje Calicles que es coherente con la presentación de este en todo el diálogo.
Πολέμου καὶ μάχης... (Gorg. 447a1 ff.): War and Virility in the Characterisation of Calicles in Plato’s Gorgias
Keywords: Plato; Gorgias; Callicles; Socrates; War; Platón; Gorgias; Calicles; Sócrates; Guerra; https://purl.org/pe-repo/ocde/ford#6.03.01